2022
DOI: 10.1002/ehf2.13687
|View full text |Cite
|
Sign up to set email alerts
|

Heart transplantation outcomes in arrhythmogenic right ventricular cardiomyopathy: a contemporary national analysis

Abstract: Aims Heart failure is an increasingly recognized later stage manifestation of arrhythmogenic right ventricular cardiomyopathy (ARVC) that can require heart transplantation (HT) to appropriately treat. We aimed to study contemporary ARVC HT outcomes in a national registry. Methods and resultsThe United Network for Organ Sharing registry was queried for HT recipients from 1/1994 through 2/2020. ARVC patients were compared with non-ARVC dilated, restrictive, and hypertrophic cardiomyopathy HT patients (HT for isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Although ARVC remains a rare disease and does not represent the majority of pathologies requiring HT, heart failure has increasingly been recognized as a later-stage manifestation of ARVC, which has led to more HTs to appropriately treat (8). Recently, researchers reviewed a registry of HT recipients from January 1994 through February 2020 to compare ARVC patients with non-ARVC patients who had dilated, restrictive, and hypertrophic cardiomyopathies (8). Consistent with other published reports, they found that ARVC patients had significantly less comorbidities (e.g., diabetes and cigarette use) when compared with non-ARVC patients and a significantly higher rate of survival (8).…”
Section: Discussionmentioning
confidence: 99%
“…Although ARVC remains a rare disease and does not represent the majority of pathologies requiring HT, heart failure has increasingly been recognized as a later-stage manifestation of ARVC, which has led to more HTs to appropriately treat (8). Recently, researchers reviewed a registry of HT recipients from January 1994 through February 2020 to compare ARVC patients with non-ARVC patients who had dilated, restrictive, and hypertrophic cardiomyopathies (8). Consistent with other published reports, they found that ARVC patients had significantly less comorbidities (e.g., diabetes and cigarette use) when compared with non-ARVC patients and a significantly higher rate of survival (8).…”
Section: Discussionmentioning
confidence: 99%
“…But, there was no patient who was implanted with a mechanical circulatory support device in this cohort. Guiliano et al reported 252 HTx wait-listed patients extracted from the UNOS database between 1994 and 2020 ( 14 ). They comprised only 0.4% of the entire HTx listed patients, but the percentage of all HTx performed for the primary indication of ARVC increased from 0.04% in 1994 to 0.73% in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Six patients (2.4%) had VADs on listing: one with LVAD, two with a TAH, and three with BiVAD. By the time of transplantation, a total of 15 patients (7.9%) had VADs: six with LVADs, two with RVADs, four with TAHs, and three with BiVAD ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, due to widespread use of implantable cardioverter-defibrillators (ICDs) to prevent sudden cardiac death, an increasing number of ARVC patients develop heart failure [8]. In advanced stages of the disease, heart transplantation should be considered but selecting optimal time for this treatment remains challenging because of the predominantly right ventricular pathophysiology [9][10]. Numerous novel biomarkers have been recently studied in cardiology, and the results suggest that some of them will be introduced into routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%